2015
DOI: 10.1039/c5sc01914a
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative benzylic–oxyallylic stabilized cations: regioselective construction of α-quaternary centers in ketone-derived compounds

Abstract: Herein we describe a direct capture of benzylic–oxyallylic stabilized carbocations with high value nucleophiles towards regioselective construction of α-quaternary centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 64 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…The highly reactive cations are generated under weakly basic conditions and trapped by neutral heteroatoms and soft π-nucleophiles. Kartika and co-workers reported regioselective nucleophilic additions to unsymmetrical oxyallyl cations under mild Brønsted acid catalysis in 2015. …”
mentioning
confidence: 99%
“…The highly reactive cations are generated under weakly basic conditions and trapped by neutral heteroatoms and soft π-nucleophiles. Kartika and co-workers reported regioselective nucleophilic additions to unsymmetrical oxyallyl cations under mild Brønsted acid catalysis in 2015. …”
mentioning
confidence: 99%
“…Later, Tang reported the reaction of α-chlorocyclohexanone with 2-naphthol . Finally, Kartika reported that 6-membered aryl-substituted α-hydroxy methylenol ethers were readily converted to the corresponding oxyallyl cations and regioselectively trapped by indoles . While each method is powerful in its own right, the classes of arenes employed (indoles/naphthols) were limited, and the number of actual examples involving cyclohexanones was small (<6 examples).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nucleophiles, including arenes, heteroarenes, alkenes and alkynes, add readily to cyclic oxyallyl cation species. This chemistry forms the basis for “interrupted” versions of the oxy -Nazarov cyclization, , and has also been developed in conjunction with a simple ionization event. To test the feasibility of a interrupted halo -Nazarov strategy, we chose to examine aldehyde 1a , which bears an electron-rich aryl group well-suited for intramolecular capture of the type 5 haloallyl cation intermediate, with irreversible formation of a new C–C bond and all-carbon quaternary center.…”
mentioning
confidence: 99%